Women with disabilities and the loss of custody of their children: "Carers, but not mothers" - Rodriguez-Garrido, Pia; Herrera, Florencia; Yupanqui Concha, Andrea; Rojas, Andrea; Hichins Arismendi, Melissa Andrea (My University, 2024)
Historically, the motherhood of women with disabilities has been questioned due to negative representations surrounding it. It is assumed that women with disabilities cannot be mothers and, when they are, their capacity to care for their children is called into doubt. According to international literature, women with disabilities are more susceptible to losing the custody of their children. However, in Chile, there is scant evidence about this.Using the paradigm of situated feminist epistemologies, this paper analyzes the experiences of three Chilean mothers with disabilities who have faced judicial processes regarding their children's custody. Three dimensions emerged from the thematic analysis: (a) The role of carers under tension: "Carers, but not mothers!"; (b) The absence of support and reasonable accommodations: The institutional debt; and (c) The influence of ableism on custody processes. The findings reveal a series of adversities that women with disabilities must overcome to demonstrate their fitness as mothers. Institutional ableism hampers due process in cases about the custody of their children. As long as appropriate support is provided and the disabling view is transformed, mothers with disabilities can provide the care and parenting their children require.
Keywords: care; chile; custody; disability; feminisms; motherhood